2014
DOI: 10.1186/gb-2014-15-1-r13
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive patterns of gene expression regulated by RNA-binding proteins

Abstract: BackgroundRNA-binding proteins regulate a number of cellular processes, including synthesis, folding, translocation, assembly and clearance of RNAs. Recent studies have reported that an unexpectedly large number of proteins are able to interact with RNA, but the partners of many RNA-binding proteins are still uncharacterized.ResultsWe combined prediction of ribonucleoprotein interactions, based on catRAPID calculations, with analysis of protein and RNA expression profiles from human tissues. We found strong in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 84 publications
7
40
0
Order By: Relevance
“…As observed for protein–protein interactions, structurally disordered regions bind with high specificity and low affinity . Hence, noncanonical domains, which are enriched in structural disorder, could promote low affinity interactions with RNA molecules . Accordingly, computational methods predict that the RNA‐binding ability of structural disorder is more pronounced in noncanonical RBPs, indicating that unfolded regions promote RNA interactions .…”
Section: Resultsmentioning
confidence: 99%
“…As observed for protein–protein interactions, structurally disordered regions bind with high specificity and low affinity . Hence, noncanonical domains, which are enriched in structural disorder, could promote low affinity interactions with RNA molecules . Accordingly, computational methods predict that the RNA‐binding ability of structural disorder is more pronounced in noncanonical RBPs, indicating that unfolded regions promote RNA interactions .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been observed that protein disorder is an important feature for RNA-binding proteins (Bellay et al , 2011; Cirillo et al , 2014). In agreement with this result, we found a significant enrichment in disorder propensities (Bhaskaran and Ponnuswamy, 1988; Campen et al , 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, the interactions of many RBPs in regulatory complexes determine specificity of PTGR processes. Hence, groups of RBPs in common PTGR pathways are often co-expressed and can drive coordinated expression of targets in cells and tissues, as well as across developmental processes 22,155,156 . Specific expression of RBPs can be used to deduce their putative roles and to identify novel components of regulatory pathways.…”
Section: Expression Dynamics Of Rbpsmentioning
confidence: 99%